THE IMPACT OF PERCEIVED STRESS ON ELEVATED RANDOM BLOOD GLUCOSE LEVELS IN TYPE 2 DIABETES MELLITUS PATIENTS - Febriani, Dita Hanna (Medical-Surgical Journal of Nursing Research, 2024)
Stress is important because it is associated with many persistent diseases, including diabetes. People with type 2 diabetes mellitus are not the only ones whose blood sugar levels can increase in response to stress. The purpose of this study was to determine whether there is a relationship between stress and fluctuating blood sugar levels. This study was a cross-sectional study of 150 patients diagnosed with type 2 DM. Data were collected from October to November 2020 in the outpatient department of a private hospital. The inclusion criteria for respondents were at least 18 years of age, in stable condition, not diagnosed with psychosis. Respondents' stress levels were assessed using the Perceived Stress Scale (PSS) and random blood glucose levels were measured using a glucometer. A total of 81 respondents were female (54%), had low education (53.9%), and were unemployed (75.3%). There was a significant relationship between perceived stress and random blood glucose levels (p = 0.047). Perceived stress had a significant relationship with random blood glucose levels.